Gambaran Hasil Pemeriksaan Hepatitis C Virus Viral Load Di RSPAD Gatot Soebroto Jakarta - Al Yasin, Fatin; Zuraida, Zuraida; Widhyasih, Retno Martini (Universitas Mohammad Husni Thamrin, 2024)
The Hepatitis C virus (Hepatitis C virus, HCV), which belongs to the Ribonucleic Acid (RNA) virus, belongs to the Flaviviridae family and the Hepacivirus genus. The entry of this virus will produce antibodies against HCV which can be measured through serological examination which indicates a history of infection. This study aims to determine the results of the HCV Viral load examination in Hepatitis C patients at Gatot Soebroto Army Hospital, Jakarta. This research was conducted descriptively using secondary data obtained from Medical Records and Clinical Pathology on the results of Viral load examinations on 225 patient data who underwent Viral load examinations. The results showed that 121 (53.8%) were detected and 104 (46.2%) were not detected. Based on the age category, high detectable Viral load results were found in the 36-45 year old age category (Lateadults) with a detected number of 27 (12%) patients, 46-55 years (Early elderly) detected 33 (14.7%) patients and age 65> (Elderly) was detected in 31 (13.8%) patients. However, in this study it was not known for sure the cause of HCV. The conclusion of this research is that Hepatitis C viral load examination is an indicator of treatment success Keyword : Hepatitis C, Age category, Gender, Viral load Libraries